Multiple Pyogenic Liver Abscess - Deepak Madi (Asian Journal of Medical Sciences, 2013)
Multiple liver abscess is a life threatening condition with high mortality. We present a case of a 59 yr old gentleman who developed multiple hepatic abscesses due to an appendicular mass. He was treated with parenteral antibiotics and ultrasound guided needle aspiration of the largest abscess was done. He recovered promptly with complete resolution of the liver abscesses. The main aim of this case report is to highlight the fact that multiple pyogenic liver abscesses can be managed with antibiotic treatment and needle aspiration.